(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This internship was conducted in the Legal Department with the aim of examining the role of legal compliance in improving the company’s financial efficiency. The study was conducted using a descriptive method with a qualitative approach. The results of the internship showed that the involvement of the Legal Department in the preparation and review of cooperation documents, such as contracts and MoUs, as well as the management of other legal documents, was able to minimize the potential for disputes and fines that had an impact on the company’s finances. The main problems faced were the lack of document digitization and the minimal understanding of non-legal units regarding the importance of legal aspects. Therefore, it is necessary to increase legal literacy in all work units and optimize digital document management. Thus, proper legal compliance has proven to be an important foundation in supporting financial efficiency and good corporate governance.